Titanium-magnesium layered composite metal material and preparation method thereof

Through alternating stacking and combining vacuum hot pressing and multi-pass hot rolling technology, the problems of uneven materials and poor bonding in the preparation of titanium-magnesium layered composite materials are solved, and a titanium-magnesium composite metal material with high plasticity, long life and density are achieved.

CN119749041APending Publication Date: 2025-04-04EAST CHINA UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510073658.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the existing titanium-magnesium layered composite materials preparation technology, there are problems such as uneven material, poor bonding, and poor plasticity, and many defects and impurities at the interface.

Method used

By alternately stacking pure titanium and magnesium alloy plates, combined with vacuum hot pressing and multi-pass hot rolling technology, a titanium-magnesium layered composite metal material was prepared. The method includes pretreatment, hot pressing composite, rolling composite and annealing processing, etc., to ensure the density of the material and the goodness of the interface bonding.

Benefits of technology

The high plasticity, long life and density of titanium-magnesium layered composite metal materials are achieved, avoiding brittle intermetallic compounds at the interface and improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119749041A_ABST
    Figure CN119749041A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a titanium-magnesium layered composite metal material. The preparation method comprises the following steps: respectively pretreating a pure titanium plate and a magnesium alloy plate; alternately laminating the pure titanium plate and the magnesium alloy plate to form a laminated structure in which the pure titanium plate is positioned on the outermost layer; under the temperature of 500-600 DEG C and the pressure of 5-20 MPa, the laminated structure is subjected to hot pressing compounding to form a pre-combined block; at the temperature of 400-500 DEG C, rolling and compounding the pre-combined block bodies to form a composite structure; and at the temperature of 350-500 DEG C, the composite structure is subjected to annealing treatment to form the titanium-magnesium layered composite metal material. The invention further relates to the titanium-magnesium layered composite metal material obtained through the preparation method. The titanium-magnesium layered composite metal material is prepared from the pure titanium plate and the magnesium alloy plate through the steps of alternate lamination, vacuum hot pressing, hot rolling and the like, the plasticity is high, the service life is long, the compactness is good, and no obvious brittle intermetallic compound exists at the interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation of composite materials, and more particularly to a titanium-magnesium layered composite metal material and a preparation method thereof. Background Art

[0002] Titanium, magnesium, and their alloys are lightweight metal materials with extensive engineering applications. Titanium, among others, is widely used in aerospace, medical, and marine applications, attracting considerable attention for its high strength-to-weight ratio, high corrosion resistance, biocompatibility, and non-toxicity. However, its high production cost and processing difficulty limit its application. Magnesium, one of the lightest metal structural materials, is used in aerospace, electronics, and military applications due to its high strength and rigidity, excellent machinability, high damping and shock absorption, and ease of recycling. However, magnesium and its alloys are severely limited in their application by their corrosion, flammability, and poor plastic deformation capacity. Therefore, combining titanium and magnesium to create a titanium-magnesium layered composite metal material with superior bonding properties would combine the advantages of both metals, namely, light weight, corrosion resistance, and strong plastic deformation capacity, with the high plasticity and long life of the layered composite material. This composite material would have broad application prospects in aerospace, electronics, marine engineering, and military applications.

[0003] In the field of materials science, the combination of titanium and magnesium metals faces a series of challenges. First, there are significant differences in the physical and chemical properties of these two metal elements. They have low mutual solubility in the solid state and it is difficult to form stable intermetallic compounds. In addition, during the processing, both titanium and magnesium metals easily react with oxygen to form an oxide layer, which further hinders the direct combination of the two metals. Due to these factors, the combination process of titanium and magnesium metals faces significant challenges in technical implementation. At present, the common preparation processes of titanium-magnesium composite materials include explosive welding, rolling composite, powder metallurgy, etc. Among them, explosive welding has high production efficiency, but too many defects at the weld affect the material properties and pose a safety hazard. Powder metallurgy can accurately control the composition of the material and has good molding, but the production efficiency is low and it is easy to produce pores. Rolling composite has become the main method for preparing layered composite materials due to its high production efficiency, good molding and simple operation. However, the existing titanium-magnesium rolling composite technology still has many problems. For example, the rolling method of sandwiching an aluminum plate between a titanium plate and a magnesium plate increases the success rate of bonding, but it is easy to generate titanium-aluminum and magnesium-aluminum intermetallic compounds, resulting in a decrease in material performance; the method of fixing the titanium plate and the magnesium plate together with rivets, iron wire, etc. for rolling is prone to cause problems such as uneven rolled samples, poor bonding performance, and impurity holes at the interface. Summary of the Invention

[0004] In order to solve the problems of uneven materials, poor bonding leading to poor plasticity, and many defects and impurities at the interface in the above-mentioned prior art titanium-magnesium layered composite metal material preparation technology, the present invention provides a titanium-magnesium layered composite metal material and a preparation method thereof.

[0005] According to the preparation method of the titanium-magnesium layered composite metal material of the present invention, it includes the following steps: S1, pretreating pure titanium plates and magnesium alloy plates respectively; S2, alternately stacking pure titanium plates and magnesium alloy plates to form a laminated structure with pure titanium plates located in the outermost layer; S3, at a temperature of 500°C to 600°C and a pressure of 5MPa to 20MPa, the laminated structure is composited by hot pressing to form a pre-bonded block; S4, at a temperature of 400°C to 500°C, the pre-bonded block is composited by rolling to form a composite structure; S5, at a temperature of 350°C to 500°C, the composite structure is annealed to form a titanium-magnesium layered composite metal material.

[0006] In a preferred embodiment, in step S1 , the pretreatment includes pickling and ultrasonic cleaning with anhydrous ethanol for the pure titanium plate, and wire brush grinding and ultrasonic cleaning with anhydrous ethanol for the magnesium alloy plate.

[0007] In a preferred embodiment, in step S3, the laminated structure is wrapped with packaging paper and placed in a mold, the mold is placed in a vacuum hot pressing furnace, heated and pressurized for 0.5h to 2h, and then taken out of the furnace after cooling to room temperature to obtain a pre-bonded block.

[0008] In a preferred embodiment, vacuum is first drawn, then inert gas is passed to expel the air, and then vacuum is drawn again to ensure that there is no residual air in the furnace. After vacuuming, the vacuum degree in the furnace is maintained at 0.01 Pa, and then the temperature and pressurization are increased.

[0009] In a preferred embodiment, heating and pressurizing include: setting an initial pressure of 1MPa~3MPa to allow the pure titanium plate and the magnesium alloy plate to fit tightly, controlling the heating rate to 10℃ / min, starting uniform pressurization when the temperature reaches 300℃~400℃, and making the pressure reach 5MPa~20MPa when the temperature reaches 500℃~600℃, and then sintering at a temperature of 500℃~600℃ for 0.5h~2h while maintaining heat and pressure.

[0010] In a preferred embodiment, in step S4, the pre-bonded blocks are placed in a muffle furnace for preheating treatment before rolling, and then rolled 5 to 11 times to obtain a composite structure.

[0011] In a preferred embodiment, the total reduction ratio is 25% to 55%, the single reduction ratio is 4% to 10%, and the rolling speed is 0.3 m / s to 0.5 m / s.

[0012] In a preferred embodiment, in step S5, the muffle furnace is heated to 350° C. to 500° C., the composite structure is placed in the muffle furnace for annealing, and then cooled to room temperature with the furnace to obtain a titanium-magnesium layered composite metal material.

[0013] In a preferred embodiment, the annealing temperature is 350° C. to 500° C., and the holding time is 60 min to 120 min.

[0014] The titanium-magnesium layered composite metal material obtained according to the above preparation method of the present invention comprises pure titanium layers and magnesium alloy layers alternately stacked.

[0015] The pure titanium plate and magnesium alloy plate of the present invention are made into titanium-magnesium layered composite metal material through the steps of alternate lamination, vacuum hot pressing and hot rolling, etc., which has high plasticity, long service life, good density and no obvious brittle intermetallic compound at the interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is an interface bonding morphology diagram of the titanium-magnesium layered composite metal material according to Example 1 of the present invention.

[0017] Figure 2 1 is an element diffusion diagram at the interface of the titanium-magnesium layered composite metal material according to Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.

[0019] The preparation method of the titanium-magnesium layered composite metal material according to the present invention first includes providing a pure titanium plate and a magnesium alloy plate. In a preferred embodiment, the pure titanium plate is a TA1 pure titanium plate. In a preferred embodiment, the magnesium alloy plate is a MgAlZn magnesium alloy. In a preferred embodiment, the magnesium alloy plate is an AZ31B magnesium alloy plate. In a preferred embodiment, the dimensions of the pure titanium plate and the magnesium alloy plate are both 75 mm long × 75 mm wide × 0.2 mm thick. In a preferred embodiment, the thickness ratio of the pure titanium plate and the magnesium alloy plate is 1:1. In a preferred embodiment, the length and width of the pure titanium plate and the magnesium alloy plate are both 1:1.

[0020] The preparation method of the titanium-magnesium layered composite metal material according to the present invention then includes pre-treating the pure titanium plate and the magnesium alloy plate separately. In a preferred embodiment, the pre-treatment includes pickling the pure titanium plate and ultrasonic cleaning it with anhydrous ethanol. In a preferred embodiment, the acid is a 10-15 vol.% HF solution. The pure titanium plate is cleaned with an HF solution for 0.5 min to 2 min, and the cleaned pure titanium plate appears silvery white. In a preferred embodiment, the pre-treatment includes wire brushing and ultrasonic cleaning it with anhydrous ethanol on the magnesium alloy plate. In a preferred embodiment, the polished magnesium alloy plate appears silvery white. In a preferred embodiment, HF solution cleaning and wire brushing are used to remove impurities such as oxidation and oil stains on the surface of the pure titanium plate and the magnesium alloy plate, respectively, and then the pure titanium plate and the magnesium alloy plate are placed in anhydrous ethanol solution for ultrasonic cleaning for 10-15 min and blown dry to expose fresh metal.

[0021] The method for preparing the titanium-magnesium layered composite metal material according to the present invention then includes alternately stacking pure titanium plates and magnesium alloy plates to form a laminate structure in which the pure titanium plates are the outermost layers. In a preferred embodiment, the pure titanium plates and the magnesium alloy plates are alternately stacked in a pattern of titanium-magnesium-titanium...magnesium-titanium-magnesium-titanium. In a preferred embodiment, there are N magnesium alloy plates and N+1 pure titanium plates. In one preferred embodiment, 13 pure titanium plates and 12 magnesium alloy plates are stacked in a pattern of titanium-magnesium-titanium...magnesium-titanium-magnesium-titanium to form a total of 25 layers.

[0022] The preparation method of the titanium-magnesium layered composite metal material according to the present invention then includes hot pressing the laminated structure at a temperature of 500°C to 600°C and a pressure of 5MPa to 20MPa to form a pre-bonded block. In particular, 500°C to 600°C is lower than the melting point of magnesium, ensuring the bonding of titanium and magnesium while controlling the molding of the material, and preparing a pre-bonded block with no impurities such as oxides and oil stains at the interface and no voids. In a preferred embodiment, the laminated structure is wrapped with wrapping paper and placed in a mold, and the mold is placed in a vacuum hot press furnace, heated and pressurized for 0.5h to 2h, and then taken out of the furnace after cooling to room temperature to obtain a pre-bonded block. In a preferred embodiment, the wrapping paper is graphite paper. It should be understood that other materials with good thermal conductivity, high temperature resistance and good demolding properties can be used in the present invention. In a preferred embodiment, the mold is a metal mold. It should be understood that molds made of other materials with good pressure resistance and thermal conductivity can also be used in the present invention. In a preferred embodiment, vacuum is first drawn, then inert gas is passed to expel the air, and then vacuum is drawn again to ensure that there is no residual air in the furnace. After vacuuming, the vacuum degree in the furnace is maintained at 0.01Pa, and then the temperature is increased and pressurized. In a preferred embodiment, the temperature increase and pressurization include: setting an initial pressure of 1MPa to 3MPa to allow the pure titanium plate and the magnesium alloy plate to fit tightly together, controlling the heating rate to 10℃ / min until the hot pressing temperature of 500℃ to 600℃ is reached, and starting to uniformly pressurize when the temperature reaches 300℃ to 400℃ during the heating process, so that the pressure reaches 5MPa to 20MPa when the temperature reaches 500℃ to 600℃, and then sintering at a temperature of 500℃ to 600℃ for 0.5h to 2h while maintaining heat and pressure. In a preferred embodiment, the pre-bonded interface of the pre-bonded block is good, flat and free of impurity pores.

[0023] The method for preparing the titanium-magnesium layered composite metal material according to the present invention then includes rolling the pre-bonded blocks together at a temperature of 400°C to 500°C to form a composite structure. In particular, the temperature of 400°C to 500°C ensures that the material softens for easy processing while preventing spontaneous combustion of the magnesium alloy, thereby increasing the success rate of composite structure preparation. In a preferred embodiment, the rollers are cleaned before rolling to prevent oxides on the rollers from adhering to the composite plate and affecting rolling uniformity. In a preferred embodiment, the pre-bonded blocks are placed in a muffle furnace for preheating before rolling, and then the composite structure is obtained through 5 to 11 rolling cycles. In a preferred embodiment, the preheating temperature is 400°C to 500°C, and the preheating time is 5 to 10 minutes. In a preferred embodiment, the total reduction is 25% to 55%, the single reduction is 4% to 10%, and the rolling speed is 0.3 m / s to 0.5 m / s. In a preferred embodiment, the intermediate heating temperature during multi-pass hot rolling is 400°C to 500°C, and the intermediate heating time during multi-pass hot rolling is 5 to 10 minutes. In particular, the multi-pass hot rolling technology controls the amount of downward pressure and rolling speed during each pass to ensure uniformity and strength of the bond between the two metal sheets, avoiding material fracture, delamination, and unevenness.

[0024] The preparation method of the titanium-magnesium layered composite metal material according to the present invention then includes annealing the composite structure at a temperature of 350°C to 500°C to form a titanium-magnesium layered composite metal material. In a preferred embodiment, the muffle furnace is heated to 350°C to 500°C, the composite structure is placed in the muffle furnace for annealing, and the furnace is cooled to room temperature to obtain a titanium-magnesium layered composite metal material. In a preferred embodiment, the annealing temperature is 350°C to 500°C, and the holding time is 60min to 120min. In particular, the titanium-magnesium layered composite metal material is well bonded at the interface, and has excellent mechanical properties of high plasticity and long life compared to single-phase pure titanium or magnesium alloys, and has the advantages of both materials such as light weight, corrosion resistance, and strong plastic deformation ability.

[0025] In this way, the present invention solves the technical problem of composite of pure titanium plate and magnesium alloy plate by combining vacuum hot pressing and multi-pass hot rolling, and prepares titanium-magnesium composite metal material with high plasticity, long life, good density and no obvious brittle intermetallic compounds at the interface.

[0026] Example 1

[0027] The pure titanium plate and magnesium alloy plate were cleaned with 10 vol.% HF solution and polished with a wire brush to remove impurities such as oxidation and oil on the surface. The metal plates were then ultrasonically cleaned in anhydrous ethanol solution for 15 minutes and blown dry to obtain metal plates with no oxide on the surface and exposed fresh metal, which were then kept for later use.

[0028] The 13 pre-treated pure titanium plates and 12 magnesium alloy plates were combined by alternating stacking, with the pure titanium plate located in the outermost layer. There were 25 layers in total according to the stacking method of titanium-magnesium-titanium...magnesium-titanium-magnesium-titanium. After being neatly arranged, they were wrapped with graphite paper and placed in a metal mold. The metal mold was placed in a vacuum hot pressing furnace, first evacuated, then argon was passed through to expel the air, and finally evacuated to maintain a vacuum degree of 0.01Pa. The initial pressure was set to 1MPa to make the pure titanium plate and the magnesium alloy plate fit tightly together, and the heating rate was controlled to 10℃ / min until the hot pressing temperature of 500℃ was reached. During the heating process, uniform pressure was applied when the temperature reached 400℃, so that the pressure reached 8.5MPa when the temperature reached 500℃. Subsequently, the material was sintered at 500℃ under heat and pressure for 1h, and finally cooled to room temperature with the furnace and taken out to obtain a titanium-magnesium layered composite metal material with good pre-bonding, a flat interface and no impurities or pores.

[0029] The titanium-magnesium layered composite metal material pre-bonded after vacuum hot pressing is placed in a muffle furnace and kept at 500°C for 10 minutes for preheating treatment before rolling; the preheated titanium-magnesium layered composite metal material is then subjected to multiple hot rolling passes with a total reduction rate of 40%, a single reduction rate of 4% to 7%, and a rolling speed of 0.3m / s. The intermediate heating temperature and time of the multiple hot rolling passes are the same as those for preheating. After 8 rolling passes, a well-bonded titanium-magnesium layered composite metal material is obtained.

[0030] The titanium-magnesium layered composite metal material is placed in a muffle furnace for annealing treatment at a temperature of 500° C. for a holding time of 60 minutes, and then cooled to room temperature with the furnace to obtain a titanium-magnesium layered composite metal material with high plasticity and long life.

[0031] According to the room temperature tensile test requirements of GB / T228.1-2021 metal materials, the tensile properties of the titanium-magnesium layered composite metal material were tested. The results are shown in Table 1. The elongation at break was 27.95%, which was 110.94% and 98.5% higher than those of pure titanium and magnesium alloy plates prepared by the same rolling method, respectively. According to the axial strain controlled fatigue test requirements of GB / T26077-2021 metal materials, the fatigue properties of the titanium-magnesium layered composite metal material were tested. The results are shown in Table 1. The fatigue life of the composite material was 2907 weeks, which was 68.52% and 52.75% higher than those of pure titanium and magnesium alloy plates prepared by the same rolling method, respectively.

[0032] like Figure 1 As shown in the figure, the interface of the composite metal material was observed by scanning electron microscopy. The interface was well bonded and there were no composite problems such as impurities, pores, and cracks. This shows that the obtained titanium-magnesium composite metal material has good density and no obvious brittle intermetallic compounds at the interface. Figure 2 As shown in the figure, the diffusion of titanium and magnesium elements at the interface was analyzed using the line scanning function of the energy spectrometer. It can be seen that the two elements diffused into each other and formed a metallurgical bond.

[0033] Example 2

[0034] The preparation steps of this embodiment are the same as those of embodiment 1, except that the vacuum hot pressing temperature is changed to 550° C. and kept for 1 hour. The test conditions of the tensile test and fatigue test remain unchanged. The results are shown in Table 1.

[0035] Example 3

[0036] The preparation steps of this embodiment are the same as those of embodiment 1, except that the vacuum hot pressing temperature is changed to 600° C. and the heat preservation time is 1 hour. The test conditions of the tensile test and fatigue test remain unchanged. The results are shown in Table 1.

[0037] Example 4

[0038] The preparation steps of this embodiment are the same as those of Example 1, except that the vacuum hot pressing temperature is changed to 600°C and maintained for 1 hour; the reduction ratio is 25%, the single reduction ratio is 4% to 6%, the total number of rolling times is 5, and the test conditions of the tensile test and fatigue test remain unchanged. The results are shown in Table 1.

[0039] Example 5

[0040] The preparation steps of this embodiment are the same as those of Example 1, except that the vacuum hot pressing temperature is changed to 600°C and maintained for 1 hour; the reduction rate is 55%, the single reduction rate is 4% to 10%, the total number of rolling times is 11, and the tensile test and fatigue test conditions remain unchanged. The results are shown in Table 1.

[0041] Table 1 Mechanical properties test results

[0042] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. Various modifications are possible. In other words, any simple, equivalent changes and modifications made in accordance with the claims and description of the present invention are within the scope of protection of the patent claims. Anything not fully described in this invention constitutes conventional technology.

Claims

1. A method for preparing a titanium-magnesium layered composite metal material, characterized in that: The preparation method comprises the following steps: S1, pretreatment of pure titanium plate and magnesium alloy plate respectively; S2, alternately stacking pure titanium plates and magnesium alloy plates to form a stacked structure with the pure titanium plate in the outermost layer; S3, at a temperature of 500° C. to 600° C. and a pressure of 5 MPa to 20 MPa, the laminated structure is composited by hot pressing to form a pre-bonded block; S4, at a temperature of 400°C to 500°C, the pre-bonded blocks are composited by rolling to form a composite structure; S5, at a temperature of 350°C to 500°C, the composite structure is annealed to form a titanium-magnesium layered composite metal material.

2. The preparation method according to claim 1, characterized in that: In step S1 , the pretreatment includes pickling and ultrasonic cleaning of the pure titanium plate with anhydrous ethanol, and wire brush grinding and ultrasonic cleaning of the magnesium alloy plate with anhydrous ethanol.

3. The preparation method according to claim 1, characterized in that: In step S3, the laminated structure is wrapped with packaging paper and placed in a mold, and the mold is placed in a vacuum hot press furnace, heated and pressurized for sintering for 0.5h to 2h, and then taken out after cooling to room temperature to obtain a pre-bonded block.

4. The preparation method according to claim 3, characterized in that: First, evacuate the furnace, then pass inert gas to expel the air, and then evacuate the furnace again to ensure that there is no residual air in the furnace. After evacuating the furnace, the vacuum degree in the furnace is maintained at 0.01Pa, and then the temperature and pressurization are increased.

5. The preparation method according to claim 3, characterized in that: The heating and pressurizing process includes: setting an initial pressure of 1MPa~3MPa to allow the pure titanium plate and the magnesium alloy plate to fit closely, controlling the heating rate to 10℃ / min, and starting to pressurize evenly when the temperature reaches 300℃~400℃, so that the pressure reaches 5MPa~20MPa when the temperature reaches 500℃~600℃, and then sintering at 500℃~600℃ for 0.5h~2h while maintaining heat and pressure.

6. The preparation method according to claim 1, characterized in that: In step S4, the pre-bonded block is placed in a muffle furnace for preheating treatment before rolling, and then rolled 5 to 11 times to obtain a composite structure.

7. The preparation method according to claim 6, characterized in that: The total reduction rate is 25% to 55%, the single reduction rate is 4% to 10%, and the rolling speed is 0.3m / s to 0.5m / s.

8. The preparation method according to claim 1, characterized in that: In step S5, the muffle furnace is heated to 350° C. to 500° C., the composite structure is placed in the muffle furnace for annealing, and is cooled to room temperature along with the furnace to obtain a titanium-magnesium layered composite metal material.

9. The preparation method according to claim 1, characterized in that: The annealing temperature is 350°C to 500°C, and the holding time is 60min to 120min.

10. A titanium-magnesium layered composite metal material obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The titanium-magnesium layered composite metal material comprises pure titanium layers and magnesium alloy layers which are alternately stacked.

Citation Information

Patent Citations

  • Light high-strength titanium-magnesium-titanium vacuum rolling composite material

    CN106180186A

  • Magnesium-titanium laminated plate with good strength and plasticity and preparation method of magnesium-titanium laminated plate

    CN114261155A

  • Multistage layered heterogeneous copper-aluminum composite material and preparation method thereof

    CN116371915A